Persepsi Generasi Z terhadap Fitur Shopee Live yang Mendorong Perilaku Pembelian Impulsif Saat Berbelanja di E-Commerce Shopee - Devina, Devina; Purwanti, Silviana; Sucipta, Johantan Alfando Wikandana; Kristian, Dony (CV. Green Publisher Indonesia, 2025)
In the increasingly growing digital era, online transactions have become popular among the public, which has made consumer behavior undergo significant changes, especially among Generation Z who are very familiar with technology and social media. One of the features that is quite popular in e-commerce platforms is Shopee Live, which combines the concept of online shopping with interactive live broadcasts. This phenomenon shows a change in the way of shopping that is not only functional but also emotional, so that it has the potential to encourage impulsive buying behavior. This research was conducted with the aim of finding out how generation z's perception of the shopee live feature, especially persuasive communication elements, can encourage impulse purchase behavior when shopping at shopee e-commerce. This study uses a descriptive qualitative approach by conducting in-depth interviews with ten Generation Z informants in the city of Samarinda using purposive sampling techniques and Miles & Huberman analysis techniques. The results of the study show that Generation Z perceives Shopee Live as a fun, practical, and easy-to-use feature for the decision-making process. They consider this feature to be able to present a more real shopping experience than ordinary catalogs. The persuasive communication element in Shopee Live contributes to increasing interest in watching and helps encourage impulsive purchasing behavior. Thus, the shopee live feature has been proven to have a role in shaping positive perceptions while encouraging impulse buying behavior among generation Z in the context of online shopping. These findings provide insight for e-commerce players in designing more persuasive communication strategies, as well as encouraging consumers to be wiser in making purchasing decisions.